2023
DOI: 10.2196/40425
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Digital Health by South Asian Communities: Scoping Review

Abstract: Background South Asian individuals experience a higher burden of chronic diseases and limited access to health care services compared with their Caucasian peers. Digital health interventions can enhance the delivery of health care, minimize health inequities, and consequently improve health status among minority ethnic groups. However, it is unclear how South Asian people view and perceive the use of digital health technologies to support their health needs. Object… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…As well as there being significant diversity within South Asian populations in the UK, South Asian populations worldwide, both in South Asian countries, and in the significant diaspora in the USA and Canada, are diverse, and may have experiences of access and engagement with healthcare that is unique to the social, political, economic environment and history. Reviews looking at the experiences of digital health for South Asian people have found limited studies in the UK [13,14]; as such, this paper is an important contribution Fig. 3 Understanding user types and opportunities for engagement with digital towards understanding how services in the UK can take into account the needs of a significant population.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…As well as there being significant diversity within South Asian populations in the UK, South Asian populations worldwide, both in South Asian countries, and in the significant diaspora in the USA and Canada, are diverse, and may have experiences of access and engagement with healthcare that is unique to the social, political, economic environment and history. Reviews looking at the experiences of digital health for South Asian people have found limited studies in the UK [13,14]; as such, this paper is an important contribution Fig. 3 Understanding user types and opportunities for engagement with digital towards understanding how services in the UK can take into account the needs of a significant population.…”
Section: Limitationsmentioning
confidence: 99%
“…There is a limited evidence base about DHI acceptability and use in the South Asian population in the UK [13,14], and existing studies draw on data collected prior to the pandemic, when digital approaches were less embedded in the health service. There is a need to understand different populations' experiences and perspectives on digital health to ensure equity in future services, and how, if it all, it has been impacted by the pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…As well as there being signi cant diversity within South Asian populations in the UK, South Asian populations worldwide, both in South Asian countries, and in the signi cant diaspora in the USA and Canada, are diverse, and may have experiences of access and engagement with healthcare that is unique to the social, political, economic environment and history. Reviews looking at the experiences of digital health for South Asian people have found limited studies in the UK [13,14]; as such, this paper is an important contribution towards understanding how services in the UK can take into account the needs of a signi cant population. While this study focussed on South Asians, as the largest minority ethnic group in the UK [15], there is need for this work to be repeated in other groups who may experience barriers to digital uptake and use, to understand their speci c needs.…”
Section: Findings In Contextmentioning
confidence: 99%
“…There is a limited evidence base about DHI acceptability and use in this population [13,14], and existing studies draw on data collected prior to the pandemic, when digital approaches were less embedded in the health service. There is a need to understand different populations' experiences and perspectives on digital health to ensure equity in future services.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the field of artificial intelligence (AI) has made remarkable progress. The applications of AI in health care have also gained attention [1][2][3][4][5]. One of the most popular forms of AI involves using a natural language processing (NLP) system.…”
Section: Introductionmentioning
confidence: 99%